(untitled) (Ustozlar uchun, 2026)
This article provides a critical analysis of modern online language learning resources. The study examines the effectiveness, advantages, and limitations of various platforms, including gamified applications, online course platforms, artificial intelligence–based tools, and language exchange services. It also evaluates the role of these resources in the language learning process, particularly their impact on the development of communicative competence and their ability to adapt to learners’ needs.Special attention is given to key issues such as the imbalance between input and output in language learning, the gap between motivation and actual mastery, and the insufficient emphasis on cultural competence. The findings suggest that online resources alone may not be sufficient for achieving high levels of proficiency; however, when integrated with traditional and interactive methods, they can significantly enhance learning outcomes.This study offers practical recommendations for language learners, educators, and developers of educational technologies.